Growth and effects of thinning of mixed and pure plantations with native trees in humid tropical Costa Rica - Piotto, D.; Montagnini, F.; Ugalde, L.; Kanninen, M. (2003)
Reforestation efforts are being promoted throughout the humid tropics in response to increased areas of deforested and abandoned or degraded lands. Farmers need technical information on species performance, plantation design and management in order to make appropriate choices of species and silvicultural techniques to achieve high productivity. In Costa Rica, government incentives have promoted the planting of native tree species, but information is still scarce on species performance and silvicultural management. The present study examines the growth and responses to thinning of native species in mixed and pure-species plantations in the Caribbean Lowlands of Costa Rica. At 9–10 years of age, the species with best growth in diameter and volume were Vochysia guatemalensis Donn. Sm., Terminalia amazonia (J. Gmell) Excell, Jacaranda copaia (Aubl) D. Don, Virola koschnyi Warb. and Vochysia ferruginea Mart. Most species had better growth in mixed than in pure-species plantations. The slower growing species Calophyllum brasiliense Cambess and Genipa americana L. grew better in pure than in mixed stands. Mixed plantations (combinations of 3–4 species) ranked among the most productive in terms of volume. Trees responded to thinning with increased diameter growth, while height was not generally influenced by thinning. Tight initial spacing and thinning with high extraction of stems can improve growth and timber quality of stands. Results of the present research are useful to improve species choices for reforestation and plantation management in the humid lowlands of Costa Rica and in other regions with similar ecological characteristics.